Evaluation of the optimal steepest ascent algorithm for focusing light through turbid media - Verma, Manish (2018)
We experimentally compare the optimal steepest ascent algorithm and the sequential method for feedback based iterative wavefront shaping. The former converges significantly faster and leads to a sharp focus behind a turbid medium.